Revisiting immune escape in colorectal cancer in the era of immunotherapy - Ijsselsteijn, Marieke Erica (Br J Cancer, 2019)
In colorectal cancer (CRC), T-cell checkpoint blockade is only effective in patients diagnosed with mismatch repair-deficient (MMR-d) cancers. However, defects in Human Leukocyte Antigen (HLA) class I expression were reported to occur in most MMR-d CRCs, which would preclude antigen presentation in these tumours, considered essential for the clinical activity of this immunotherapeutic modality. We revisited this paradox by characterising HLA class I expression in two independent cohorts of CRC. We determined that loss of HLA class I expression occurred in the majority (73–78%) of MMR-d cases. This phenotype was rare in CRC liver metastases, irrespective of MMR status, whereas weak, inducible expression of HLA class I molecules was frequent in liver lesions. We propose that HLA class I is an important determinant of metastatic homing in CRCs. This observation is paramount to understand CRC carcinogenesis and for the application of immunotherapies in the metastatic setting.